Involuntary reestablishment: integration and civilization (2003)
The article exposes in a clear way the reality of the Colombian cities as far as its factors of growth, planning and organization, where the subject of the involuntary reestablishment probably arises as consequence and as only inmediate solution to the serious problems that the population face. The Involuntary reestablishment face more serious consequences than its self causes. In addition to be no wished processes they have like obligatory aim the integration, the insertion in a weave and within a consolidated society that by ignorance and fear excludes, generating great sectors of ¨excluded¨ which are difficult to handle by the existing policies. Nevertheless some restlessness with respect to the possible forms of intervention and solution of this problem consider so that as much economic level as social it does not continue affecting so gravely the Colombian cities.